Partial purification and some properties of a T2 ribonuclease from Aspergillus flavipes - Gomes, Eleni [UNESP] (1996)
A ribonuclease was partially purified from the culture medium of Aspergillus flavipes (IZ:1501), after 96 h of cultivation by chromatography on DEAE-cellulose and Sephadex G100 columns. The molecular weight of the RNase was estimated to be 40 kD by gel filtration using Sephadex G100, and the optimum pH and temperature were 4.0 and 50-55°C, respectively. Catalytic activity was inhibited by Zn+2, Fe+3, Hg+2 and Ag+ ions. The enzyme did not show an exact base specificity and produced four kinds of 3′-nucleotides from yeast RNA.